Quantitative and qualitative plant-pathogen interactions call upon similar pathogenicity genes with a spectrum of effects - Langlands-Perry, Camilla; Pitarch, Anaïs; Lapalu, Nicolas; Cuenin, Murielle; Bergez, Christophe; Noly, Alicia; Amezrou, Reda; Gélisse, Sandrine; Barrachina, Célia; Parrinello, Hugues; Suffert, Frédéric; Valade, Romain; et al. (Frontiers in Plant Science, 2023)
Septoria leaf blotch is a foliar wheat disease controlled by a combination of plant genetic resistances and fungicides use. R-gene-based qualitative resistance durability is limited due to gene-for-gene interactions with fungal avirulence (Avr) genes. Quantitative resistance is considered more durable but the mechanisms involved are not well documented. We hypothesize that genes involved in quantitative and qualitative plant-pathogen interactions are similar. A bi-parental population of Zymoseptoria tritici was inoculated on wheat cultivar 'Renan' and a linkage analysis performed to map QTL. Three pathogenicity QTL, Qzt-I05-1, Qzt-I05-6 and Qzt-I07-13, were mapped on chromosomes 1, 6 and 13 in Z. tritici, and a candidate pathogenicity gene on chromosome 6 was selected based on its effector-like characteristics. The candidate gene was cloned by Agrobacterium tumefaciens-mediated transformation, and a pathology test assessed the effect of the mutant strains on 'Renan'. This gene was demonstrated to be involved in quantitative pathogenicity. By cloning a newly annotated quantitative-effect gene in Z. tritici that is effector-like, we demonstrated that genes underlying pathogenicity QTL can be similar to Avr genes. This opens up the previously probed possibility that ‘gene-for-gene’ underlies not only qualitative but also quantitative plant-pathogen interactions in this pathosystem.